Impact of the 2024 Noto Peninsula Earthquake on Hokuriku Electric Power Company’s Shika Nuclear Power Station in Japan - Hiramoto, Kenichiro; Shaw, Rajib (Prevention and Treatment of Natural Disasters, 2024)
On January 1, 2024, at 16:10, a magnitude 7.6 earthquake struck the Noto region of Ishikawa Prefecture. The maximum seismic intensity of 7 was observed in Shika Town in the Noto region. About 10 minutes after the earthquake, a major tsunami warning and other related advisories were issued. The Japan Meteorological Agency designated this event as the “2024 Noto Peninsula Earthquake.” The Shika Nuclear Power Station, operated by Hokuriku Electric Power Co., is located in the town. This paper reviews the damage to the Shika Nuclear Power Plant over the past month from the perspective of industrial accidents (NATECH) caused by natural hazards, as well as the responses to such events. Although the plant had already implemented safety measures in line with the "New Regulatory Standards" introduced after the 2011 Fukushima Daiichi Nuclear Accident, it was struck by tremors exceeding expectations. While no external radioactive spills occurred, there were reports of water leaks from the spent fuel storage pool, oil leaks from transformers, tsunami impacts, and damage to power transmission lines. Discussions by the Nuclear Regulatory Authority also highlighted issues with radiation monitoring posts. In addition, many evacuation routes were rendered unusable. Of the 11 national and prefectural roads designated as evacuation routes for the Shika Nuclear Power Station, seven were closed due to landslides or cracks. Furthermore, the repeated high intensity and frequency of aftershocks made it difficult for residents to evacuate or take appropriate radiation protection measures, even in their homes or designated shelters. Although the disaster did not escalate into a severe nuclear crisis involving radiation leakage, the adequacy of preparedness, timely communication, and the application of lessons from past events are once again being called into question, highlighting the need to protect lives, property, and the global environment.